Psychological states underlying excellent performance in professional golfers: "Letting it happen" vs. "making it happen". (March 2016) - Swann, Christian; Keegan, Richard; Crust, Lee; Piggott, David
Abstract: Objectives: In this study we aimed to better understand the occurrence and experience of flow in elite golf. As flow is more likely to occur during peak performances, and for elite athletes, our objectives were to: (i) identify golfers who achieved exceptional performances (e.g., winning a professional tournament), and (ii) explore if and how they experienced flow within that performance. Design: Mixed-method multiple case study. Method: Participants were 10 professional golfers ( M age = 30; SD = 9.9). Performance data and participant observations informed semi-structured interviews which took place as soon as possible after an excellent performance ( M = 4 days). Data were interpreted using within-case then cross-case thematic analysis. Results: These golfers reported that they experienced two different psychological states during their excellent performances. These states were described as: (i) "letting it happen" which corresponded with the definition and description of flow; and (ii) "making it happen" which was more effortful and intense, involved a heightened awareness of the situation, and therefore differed to flow. Both states occurred through different processes, and "letting it happen" was a relatively gradual build-up of confidence, whereas "making it happen" was a more sudden stepping-up of concentration and effort. Conclusion: These findings are discussed in relation to existing literature on flow and related optimal psychological states in sport. Recommendations are then made for future research into the experience and occurrence of both states reported in this study. Highlights: Mixed-method data were collected from professional golfers' excellent performances. Two distinct psychological states were reported to underlie these performances. "Letting it happen" corresponded with the description and definition of flow. "Making it happen" was more effortful and intense, and therefore different to flow. Both states occurred through separate processes and goals, which are described.